Multi-Objective Optimization of Stress Concentration Factors for Fatigue Design of Internal Ring-Reinforced KT-Joints Undergoing Brace Axial Compression - Adnan Rasul; Saravanan Karuppanan; Veeradasan Perumal; Mark Ovinis; Mohsin Iqbal (Civil Engineering Journal, 2024)
Stress concentration factors are important to determine fatigue life based on the S-N curve methodology, where the lower the stress concentration factor, the higher the fatigue life. In this work, we developed internal ring-reinforced KT-joints, one of the most commonly used joints in the offshore industry, for the most practical ranges with the least stress concentration factors, followed by the formulation of a novel set of parametric equations for determining the stress concentration factors of internal ring-reinforced KT-joints. Using numerical investigation based on a finite element model and a response surface approach with 8 parameters (λ, δ, ψ, ζ, θ, τ, γ, and β) as input and eleven outputs (SCF 0° to SCF 90° and peak SCF), the stress at ten locations around the brace was evaluated, since efficient response surface methodology has been proven to give comprehensive and accurate predictions. The KT-joint with the following parameters: λ=0.951515, δ=0.2, ψ=0.8, ζ=0.31, θ=45.15°, τ=0.60, γ=16.25, and β=0.40 had the least stress concentration factor. The KT-joint with the optimized parameters was validated through finite element analysis. The resulting percentage difference was less than 6%, indicating the applicability of the response surface methodology with high accuracy. Doi: 10.28991/CEJ-2024-010-06-03 Full Text: PDF